'I try my best … I try to relieve the burden of my mum': a narrative analysis of the everyday care-giving experiences for five intergenerational Singapore-Chinese families where one member has dementia. Issue 8 (14th August 2021) - Koo, May Yeok; Pusey, Helen; Keady, John
Abstract: Singapore is experiencing a rapid growth in its ageing population with most of the islands' inhabitants living in high-rise apartments due to the scarcity of land. The Chinese community living in Singapore comprises the largest ethnic group and they are more likely to live together under one roof in an intergenerational family grouping. Currently, there are gaps in understanding intergenerational Singapore-Chinese families and their approach to caring at home for a family member with dementia. The aim of this longitudinal qualitative study was to understand better this everyday care-giving experience. Using semi-structured biographical interviews and digital photographs to elicit family stories, five intergenerational Singapore-Chinese families were visited at home for a period of between six and 15 months. Each recruited intergenerational family was treated as a 'case'. Narrative analysis of the data was applied within and between cases and resulted in the emergence of three themes that represented various dynamics in the data. The three themes were identified as: (1) family values, which is about the cultural context in which everyday care takes place, the religious beliefs and practices of the intergenerational Singapore-Chinese families, and the practice of filial piety; (2) family support, which is about everyday access to family and service networks, including the contribution of the live-in maid in caring for the family member with dementia; and (3) family bonds, which is about the maintenance of intergenerational family relations in the Chinese family kinship system.